PENERAPAN NETWORK MONITORING SYSTEM (NMS) SECARA VISUAL PADA INFRASTRUKTUR JARINGAN FISIK BERBASIS WEB - Annur, Haditsah; Laari, Ramdan A (Nusantara of Engineering (NOE), 2022)
A Network Monitoring System (NMS) is a system that continuously monitors the network and provides immediate notification to network administrators in the event of problems or interruptions. This study aims to apply a Network Monitoring System for monitoring network devices in Universitas Ichsan Gorontalo. This application is visually web-based, so network administrators can easily find problems with network devices in this system. As a result of this study, the system can now find problematic network devices on existing network devices. It can show the results in a visual format. If the network device check fails, the system recognizes if there is a problem with the network device.